A tentative tale of Stone Age human dynamics in Pleistocene south-western Libya (central Sahara). (November 2021) - Cancellieri, Emanuele
Abstract: The area encompassing the Acacus and Messak mountains in South Western Libya, similarly to the other central Saharan massifs, is characterized by a deeply eroded landscape where Quaternary geo-archaeological archives are rare, especially Pleistocene ones, making it difficult to understand and contextualize past human dynamics within a solid chrono-paleoenvironmental framework. Except for the few caves and open-air contexts where Pleistocene sedimentary sequences are preserved, the vast majority of archaeological evidence from the region is represented by lithic artefacts found on the surface of deflated open-air sites. Nonetheless, artefacts still stand as the main references used to build a rough framework for population dynamics through time. Although the evidence is not as solid as we would like, it allows us to at least reconsider connecting the human presence solely to 'green' phases, as a number of population dynamics related to arid landscapes have inferably occurred in the late Middle Pleistocene and in the Late Pleistocene. Coping with changing or difficult ecological settings could have been a driver at different times for behavioral adjustment, large scale displacement, increased interactions between populations and diffusion of technological innovations.